Comparison of granulated lactose properties produced by various wet granulation methods without the use of binders - A. E. Baldaev; V. V. Vaitman; Ya. G. Shopina; S. A. Kedik; A. V. Panov (Разработка и регистрация лекарственных средств)
Introduction. Direct compression is one of the most preferred methods for the production of tablet dosage forms in terms of efficiency, since it allows you to minimize the technological process down to the level of "mixing-tableting-filling and packaging". However, this method requires excipients that have appropriate flowability and compressibility. One of the widely used examples of such excipients is granulated lactose. In this work, samples of pure granulated lactose were produced by fluid bed granulation and high shear granulation in order to compare the technological properties of the product obtained using different technologies.Aim. Selecting the preferred method for producing granulated lactose using the wet granulation method without the use of binders.Materials and methods. Lactose 80 mesh (Ningbo Samreal Chemical Co., Ltd., China and Aurora Industry Co. Ltd., China), lactose 200 mesh (DMV-Fonterra Excipients GmbH & Co KG, Germany) were used as raw materials. A Hüttlin fluid bed was used for granulation and for drying. High-shear granulation was performed in high-shear mixer-granulator Evio G10H (LLC "PharmTechnologies", Russia). Tableting was carried out on a rotary tablet press. Vibrating sieves, bulk density tester and flowability tester were used for the analysis of powders, and strength and disintegration testers were used for the analysis of tablets.Results and discussion. Three approaches to obtain lactose for direct compression were tested: 1) lactose granulation in a fluidized bed; 2) modifying the surface of lactose 80 mesh particles by spraying lactose solution in a fluidized bed; 3) lactose high-shear granulation. Flowability was chosen as the first acceptance criterion for evaluating the obtained samples. When the required flowability was achieved, we proceeded to tableting the model mixture. The results obtained demonstrate that the best product is obtained by high-shear granulation.Conclusion. A comparison was made of different methods for producing granulated lactose. Based on the comparison results, shear granulation technology was selected. The properties of the resulting granulate and model tablets meet the established acceptance criteria.